Principal Strategic Management In Improving The Quality Of Education - Palah, Saepul; Wasliman, Iim; Sauri, Supyan; Andriana Gaffar, M. (CV. Inara, 2022)
This research is motivated by the phenomenon that the quality of education is still low because there are still many principals who have not implemented strategic management. Therefore, the focus of this research is that it is known that there are still many principals who have not optimally carried out strategic management so that it affects the quality of education. Another thing is also known that there are principals who do not have adequate competence, coupled with the lack of infrastructure, lack of support from the community and government, or stakeholders. This research is generally to obtain an overview of analyzing the strategic management of school principals in improving the quality of education at three Vocational High Schools (SMK) in Sukabumi Regency, namely SMK Yasidik Parakansalak, SMK Terpadu Al-Ittihad Purabaya and SMK Hassina Sukaraja. Specifically to describe and analyze the principal's strategic management in improving the quality of education, which includes: strategic environmental analysis, formulation of strategic management, implementation of strategic management, supporting and inhibiting factors of strategic management, evaluation of strategic management. The theories and concepts used in this study are strategic management theory according to the theory of quality education, the concept of principals and learning. The method used is descriptive method with qualitative data types. Data was collected through observation, interviews, and documentation studies. Data analysis was carried out by collecting all information, reducing data, presenting data and drawing conclusions. The results showed that the principal's planning was developed on the basis of the results of the assessment or evaluation in the previous year and contained development priorities with targets for achievement in the short, medium and long term. The implementation of strategic management is carried out through a series of managerial decisions and actions to determine school performance within a certain time span which in general have been in synergy with the internal environment. The supporting factors for the principal's strategic management, namely: the competence of the principal and the involvement of internal school parties in every policy formulation, while the inhibiting factors for the principal's strategic management, namely: ineffective communication between the principal and teachers and education staff, with parents students, as well as a lack of discipline and responsibility for efforts to improve school quality. The evaluation of the strategic management of improving the quality of education is carried out by the principal for teachers through meetings and other meetings to review external and internal factors encountered, to measure the performance of teachers and education personnel, and to further develop corrective actions on deviations that occur in schools.